Role of the Matching Familiar Figures Test-20 in the Analysis of Theoretical Validity of the Reflection-Impulsivity: A Study with Personality (2008)
The present study analyzes the theoretical validity of the cognitive style reflection-impulsivity with an approach based on cognition. For this purpose, it is explored the relationship between personality and reflection-impulsivity. The Matching Familiar Figures Test 20, MFFT-20 (Cairns & Cammock, 1978) was used. This test has not been employed in previous investigations with the same goal. However, the MFFT-20 has proved to be the most reliable test to assess reflection-impulsivity in children between six and twelve years old, and is the one recommended by specialized bibliography. The assessment of personality was made by means of the Spanish adaptation of the Children´s Personality Questionnaire, CPQ (Porter & Cattell, 1979). Results obtained from a sample of 94 participants between eleven and twelve years old indicate the inexistence of correlation between the studied dimensions of personality and reflection-impulsivity. As hypothesized, the only consistent and significant relationships were those of the scale of mental ability in the CPQ, and the dimension dominant-submissive, both interpreted within the frame of cognitive styles. Obtained data support the theoretical validity of the reflection-impulsivity with an approach based on cognition, as well as the divergent validity of the MFFT-20 for a sample of Spanish children.